The Highlanders’ cottage as the environment of family life in Podhale (19th century – beginning of the 20th century) - Haratyk, Anna (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
Home is a special place for every human being. Along with the family it typicallyconstitutes the basic upbringing environment and satisfies the primary needs of security,love, and family warmth. The Highlanders of the Podhale region can take pride in their exceptionally beautiful cottages, constructed of simple materials, but made with precision and with attention given to the smallest details. The above paper presents a typical cottage in Podhale with its equipment, functions, and space for all its inhabitants. It emphasises the Highlanders’ great attachment to tradition and their concurrent openness to introducing new solutions while preserving the most important, specific elements in construction that are passed down from generation to generation.
Keywords: highlanders' cottage; highlanders outfit; home